ChemInform Abstract: Asymmetric Hydrogenation of Thiophenes and Benzothiophenes. Issue 9 (5th March 2013) - Urban, Slawomir; Beiring, Bernhard; Ortega, Nuria; Paul, Daniel; Glorius, Frank
Abstract Various thiophene substrates are subjected to optimized conditions A), where high enantioselectivities are obtained in some cases.